ESG ARCHITECTURE DESIGNING TRIPLE NEXUS SYNERGIES: MULTIDIMENSIONAL CORPORATE PERFORMANCE UNDER SUSTAINABILITY RISK - Wulandari, Linda Ayu (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2026)
This study examines how green accounting (PROPER), ESG architechture (Environmental, Social, Governance), and management efficiency jointly determine multidimensional financial performance (ROA, ROE, NPM, and Sales Growth). It further evaluates the moderating role of sustainability risk (DER). Data was gathered from sustainability report of 27 basic material’s sector companies in IDX achieving PROPER’s rank during 2019-2024, through quantitative approach with using panel data on moderating regression analysis method by EViews 13. The findings reveal that Green Accounting improves corporate performance selectively by increasing profit margins but does not significantly influence broader profitability indicators or growth. ESG Architecture demonstrates uneven impacts, where environmental disclosure strengthens shareholder returns, social disclosure reduces asset efficiency, and governance disclosure shows no significant financial effect. In contrast, management efficiency consistently drives profitability and growth, highlighting the central role of operational capability in sustaining corporate performance. Moderation analysis further shows that sustainability risk does not alter the impact of Green Accounting, weakens the effectiveness of ESG practices, but conditions the performance impact of managerial efficiency. These findings highlight that sustainability initiatives alone do not guarantee financial improvement unless supported by strong managerial efficiency and balanced financial risk. The study contributes by introducing an integrated Triple Nexus ESG Architecture framework linking sustainability accounting, managerial capability, and financial risk in explaining multidimensional corporate performance.